Peran Big Data dalam Meningkatkan Efektivitas Sistem Informasi Kesehatan - Tira, Rika Iyut; Nasution, Istifani; Apriani, Elisa; Purba, Sri Hajijah (Al-DYAS, 2025)
Big data has an important role to play in the transformation of health information systems, enabling large-scale management of data coming from various sources, such as electronic medical records, epidemiological data, and wearable devices. This study aims to explore the role of big data in improving the effectiveness of health information systems. This study is expected to make theoretical and practical contributions, especially for managers and policymakers in the health sector, to strategically utilize big data in improving quality health services. This study uses the library research method to explore the role of big data in improving the effectiveness of health information systems. The data collection technique was carried out by examining literature sources from academic databases such as PubMed, ScienceDirect, Indonesian journal portals, and academic reference books. The results show that Big Data utilizes information from various sources to optimize health services, including disease prediction and evidence-based policies. The main challenges include data security and infrastructure, but the impact is significant in improving the quality of healthcare services in the digital era. In conclusion, Big data is revolutionizing health information systems through large-scale data analysis, supporting early detection, strategic planning, and evidence-based decision-making. Despite facing challenges such as data privacy and infrastructure needs, proper implementation can improve the efficiency and quality of global health services.